2012
DOI: 10.1007/s00535-011-0520-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of colorectal cancer morphology in relation to sex, age, location, and family history

Abstract: Location is the factor that has the most influence on tumor morphology. The results support the idea that different carcinogenic mechanisms may be involved in the right and left colon. Age is the most important determinant for the presence of multiple tumors and is a crucial factor for the aggressiveness of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 44 publications
3
31
1
2
Order By: Relevance
“…Carcinogenetic agents in the local environment accumulate more in the distal colorectum than in the proximal colon. Tumor microenvironments were also different according to tumor location, with more peritumor lymphocytes and more tumor-infiltrating lymphocytes in proximal tumors than in distal ones[39]. All these factors may contribute to the superior outcomes in older patients with RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenetic agents in the local environment accumulate more in the distal colorectum than in the proximal colon. Tumor microenvironments were also different according to tumor location, with more peritumor lymphocytes and more tumor-infiltrating lymphocytes in proximal tumors than in distal ones[39]. All these factors may contribute to the superior outcomes in older patients with RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors arising from the proximal colon also tend to have a different symptomology, often presenting with subtle signs and symptoms such as microcytic anemia and weight loss, as opposed to rectal bleeding and alteration in bowel habit, which are more evident in LCRC. Furthermore, higher TNM-stage, larger tumors, increased frequency of vascular invasion, mucinous type, high grade and invasive tumor border were more common features of RCC, whereas annular and polypoid tumors were more common in LCRC [15][16][17].…”
Section: Presentation and Symptomologymentioning
confidence: 96%
“…Additionally, Ghazi et al's analysis over 1600 colorectal tumors showed TIL was significantly more common in proximal colon cancer on multivariate analysis after considering other morphological features [17].…”
Section: Immunological Differencesmentioning
confidence: 98%
“…Furthermore, gross macroscopic differences are well described between proximal and distal colorectal tumours 9 11–14. In the early 1980s, epidemiological studies drew attention to sex and age disparities in site-specific colon cancer incidence, while contemporaneous reports highlighted an apparent upward trend in the incidence ratio of proximal to distal cancers 3 16 17.…”
Section: The Evolution Of the Two-colon Conceptmentioning
confidence: 99%